Rehabilitation with full of metal-ceramic crowns and conventional removable partial prosthesis - Lara Téllez, Lourdes (2009)
The treatment was performed in a female patient 67 years old, with good health status, who came wearing an uncomfortable, for their physiological and aesthetics functions, removable partial dental prosthesis. At initial examination the patients shows an upper removable partial dentures with a great incisal and occlusal wear, poor support and retention, with loss of vertical occlusal dimension, loss of facial contour, Class II Kennedy 2 edentulism, with preserved alveolar ridge and f 1.7 1.3 and 2.3 as the only present teeth. In the lower arch There was partial edentulism Class III modification 1t, without actual denture with very reabsorbed alveolar ridge, with 3.8, 3.4, 3.3, 3.2, 3.1, 4.1, 4.2, 4.3, 4.4, 4.5 and 4.8 as the actual teeth It was restored VOD by making metal ceramic crowns islands with metal supports and occlusal reciprocal arms for 1.7, 3.8 and 4.5 abutments. It was made a lingual plate on 1.3 and 2.3, in the upper and lower removable partial dental prosthesis. We shall now proceed to restore occlusal morphology giving over bite and over jet, cuspid guidance and protective occlusion . Aesthetically, It was restored upper vestibular contour loss with specific line smile.